Preliminary studies on the performance of accessions of tropical fine stem stylo (Stylosanthes guianensis sw. var. guianensis) in the eastern plains of Colombia - Grof, B (1983)
Agronomic assessment of 76 accessions of tropical fine stem stylo or "tardio" (Stylosanthes guianensis Sw. var. guianensis) was carried out at the Carimagua Research Station in the eastern plains region of Colombia. Of 27 accessions tested for dry matter yield, CIAT 10136 was the highest yielder and the most resistant to anthracnose and stemborer. In another experiment with 33 accessions, CIAT 2362 showed a high degree of tolerance to disease and insect attack, and only four maintained 75% or more of the original plant population in the second wet season. Seed yield of CIAT 10136 was reduced by 65% when there was no insect control.